THE EFFECT OF LOCAL ANESTHESIA ON HEALING TIME PERINEUM WOUNDS ON NIFAS' MOTHER AT PMB NUNUNG TANGERANG - Istighfarin, Maria; Sutarno, Maryati (HEARTY, 2025)
Background: WHO in 2020, stated that maternal deaths during pregnancy, childbirth and postpartum were 295,000 worldwide. Africa, Sub-Saharan and South Asia account for about 86%. Meanwhile, the maternal mortality rate in Indonesia in 2020 is 230 per 100,000 live births. One of the causes of maternal death is bleeding and infection. Suturing perineal tears with anesthesia is one of the maternal care programs, which aims to reduce the pain experienced by mothers during the suturing process of birth canal wounds. Giving anesthesia can also cause damage to the immune system which results in a decrease in body resistance so that there will be a lengthening of wound healing 2-3 days than without anesthesia. Research Objective: Knowing the administration of local anesthesia on the healing duration of perineal wounds in puerperal mothers. Research Method: Quasi-experiment with post-test group design. The samples in this study were all postpartum mothers who experienced perineal injuries at PMB Nunung in November-December 2023 as many as 40 people. The sampling technique uses the total sampling technique. Results of the study: The frequency distribution of long healing of perineal wounds in the majority intervention group was slow and in the majority control group was fast. The effect of local anesthesia on the healing time of perineal wounds in puerperal mothers (p. value 0.000). Conclusion and Suggestion: The effect of local anesthesia on the healing time of perineal wounds in puerperal mothers. It is expected that midwives provide counseling to postpartum mothers to properly care for perineal wounds and eat nutritious foods to accelerate the healing of perineal wounds.